Physical activities awareness and practice among the healthcare professions students in Saudi Arabia - Eidan M. Al Zahrani; Salah H. Elsafi; Abdulwahab H. Alharbi; Wadha S. Alotaibi; Aqeelah A. Alyahya; Sarah A. Alqahtani; Shatha M. Al Thabet; Shrooq O. Al Harbi; Ahmed A. Adam; Abdallah A. Al Shehri (Frontiers in Public Health)
ObjectiveThis study aimed to measure and correlate the level of awareness, attitude, and practice of physical activity among healthcare professional students with various demographical variables.MethodsThis cross-sectional study used a structured online questionnaire. A heterogeneous purposive sample, according to the study’s objectives, of health professional students belonging to 15 universities in Saudi Arabia from February to May 2024.ResultsThe overall knowledge, positive attitude, and practice scores of the participants towards the physical activity guidelines were moderate as represented by 68.97%, 47.93 %, and 51.90%, respectively. Unlike knowledge and attitude, practice varies among all demographic features. Participants identified walking as the most common form of exercise, 60.64%, followed by moderate-intensity activity,16.15%, and vigorous-intensity activity, 9.17%, while 14.04% reported no practice. Barriers to practice PA included lack of time, 55%, lack of interest, 30%, and illness/injury, 6%. There was a significant relationship between the mean practice score and both knowledge and attitude scores (p = 0.001 and 0.003, respectively).ConclusionThe study indicated a relatively moderate awareness and practice of physical activity that varied according to the demographic features due to regional differences in educational systems, cultures, and socioeconomic classes. The study highlighted the possibility of focused interventions to close the knowledge-behavior gap and encourage active lives in this community.